INFLUENCE OF GALANT SUPER APPLICATION TIME AND RATES IN CONTROL JOHNSON GRASS (Sorghum halepense) (L.) Pers. IN COTTON CROP (Gossypium hirsutum) - Arshad Thanoon Al-Niaumi (Mesopotamia Journal of Agriculture)
A factorial experiment was conducted in the season 2004 to study the effect of Galant super herbicide for controlling Johnson grass in cotton crop with two factors, the first : two time of application (after irrigation) and after a week of irrigation , and the second four rates (0 , 2 , 3 , 4 m/Liter) of herbicide in split plot system with RCBD at the fields of technical institute of Mosul –Al namrood location using Koker-310 variety of cotton to study the characters of plant height , No. of fruiting branches , stem diameter , No. bolls per plant , boll weight and seed cotton yield . Both time and rates of spraying herbicide and the interaction between them had height effect in reducing No. of plant and plant height of Johnson grass which calculated in the end of season . The No. bolls per plant and boll weight affected significantly at 1% of probability with spraying time , the application rates affected significantly for all characters except seed cotton yield , while the interaction between the two factors had significant effect on No. bolls per plant . Spraying Galant super in concentration 4ml./liter significantly increasing almost all characters of cotton , and spraying after a week of irrigation significantly increasing No. bolls per plant and boll weight which reflects to non significant increasing of seed cotton yield . It’s important to study applying higher concentrations of this herbicide in controlling Johnson grass in cotton fields in future .